2021
DOI: 10.3390/catal11091021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Catalyst Calcination Temperature on Catalytic Decomposition of HFC-134a over γ-Al2O3

Abstract: This paper explores the thermal and catalytic pyrolysis of HFC-134a over γ-Al2O3 calcined at temperatures of 550 °C (A550), 650 °C (A650), 750 °C (A750), and 850 °C (A850). The physicochemical properties of catalysts were studied through thermogravimetric analysis (TGA), Brunauer–Emmett–Teller equation for nitrogen physisorption analysis (BET), X-ray diffraction (XRD), and temperature-programmed desorption of ammonia (NH3-TPD). The non-catalytic pyrolysis of HFC-134a showed less than 15% decomposition of HFC-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Higher temperatures resulted in changes of the surface nitrogen functional groups derived from dopamine hydrochloride, but had little effect on the surface acidity which primarily originates from Al 2 O 3 . 49 The acidity and basicity of the catalysts prepared at different thermal treatment temperatures are presented in Table 2. These data indicated that 10-Al 2 O 3 -NC (550) possessed the largest amount of basic sites on its surface and the highest ratio of basic to acid sites.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Higher temperatures resulted in changes of the surface nitrogen functional groups derived from dopamine hydrochloride, but had little effect on the surface acidity which primarily originates from Al 2 O 3 . 49 The acidity and basicity of the catalysts prepared at different thermal treatment temperatures are presented in Table 2. These data indicated that 10-Al 2 O 3 -NC (550) possessed the largest amount of basic sites on its surface and the highest ratio of basic to acid sites.…”
Section: Catalyst Characterizationmentioning
confidence: 99%